Asymptomatic sensitization to a cow’s milk protein induces sustained neuroinflammation and behavioral changes with chronic allergen exposure - Brishti, Afrina; Germundson-Hermanson, Danielle L.; Smith, Nicholas A.; Kearney, Angela E.; Warda, Yassmine; Nagamoto-Combs, Kumi (Frontiers in Allergy, 2022)
Mouse models of food allergy have contributed to our understanding of various aspects of the disease, including susceptibilities, symptom spectra, cellular mechanisms, and therapeutic approaches. Previously, we used a mouse model of non-anaphylactic cow’s milk allergy (CMA) and investigated sex- and strain-dependent differences in immunological, neurological, and behavioral sequelae. We showed that male C57BL/6J mice sensitized to a bovine whey protein, β-lactoglobulin (BLG; Bos d 5), exhibited anxiety- and depression-like behavior upon acute allergen challenge. Systemic levels of BLG-specific immunoglobulins, cytokines and chemokines were also elevated in the sensitized mice. Furthermore, neuroinflammation and intestinal dysbiosis were evident as the possible causes of the altered behavior. To assess whether frequent allergen exposure influences CMA-associated pathologies over an extended period in this subclinical model, we placed BLG-sensitized mice on a whey protein (WP)-containing or whey-free control (CTL) diet for 3 months. As expected, allergen-specific IgE was significantly elevated in the plasma after completing the 5-week sensitization phase. However, the IgE levels declined in both diet groups after 3 months. In contrast, allergen-specific IgG1 stayed elevated in sensitized mice with the CTL diet, and the WP diet to a lesser extent. Interestingly, BLG-sensitized mice on the WP diet exhibited anxiety-like behavior and a trend toward spatial memory decline compared to the sham or the sensitized mice on the CTL diet. Moreover, increased immunoreactivities for GFAP and Iba1 and elevated levels of CXCL13 and CCL12, the chemokines involved in central leukocyte recruitment and other neurological diseases, were also observed in the brain. We demonstrated that sensitization to the whey protein, particularly with continuous allergen exposure, resulted in persistent neuroinflammation and associated behavioral changes despite lowered allergen-specific immunoglobulin levels. These results suggested that continuous consumption of the offending allergen may lead to adverse consequences in the brain even after desensitization.